Acidente de trabalho típico : uma análise da binarização da culpa - Luz, Leonardo Del Puppo (2009)
Accidents in the workplace have been a broadly discussed topic in society. The government registered 653,090 accidents in 2007. 414,785 (80,7%) of them happened during the working hours (called typical accidents). Facing these results, several public agencies are working hard to avoid this kind of accidents using some laws and decrees based on the Brazilian constitution from 1988. Each branch of these agencies seeks for solutions to decrease these accidents.These investigations, which took place in the state of Espírito Santo Brazil, analyzed common speeches and devices, specially the ones related to operations. This methodology can be blamed for two different reasons: in some cases the investigative tools affirm or even praise the insecure acts , in other cases the lack of attention when following the working security rules. The public agencies which were part of the research were: Ministério Público do Trabalho (Procuradoria Regional do Trabalho da 17ª Região) , Ministério do Trabalho e Emprego (Superintendência Regional do Trabalho e Emprego/ES) - both dealing with working matters and the Polícia Civil (Delegacia Especializada em Acidente de Trabalho) police branch specialized in accidents in the work place. Surveys and document analysis were ways proposed as source of data.As a result, the research seeks for the reasons to be blamed as cause of the accidents. It uses the Michel Foucault s concept of biopower as theoretical basis investigating the source of this guilt. As introduced by Deleuze a cartography building will used as methodology. The creation of a method that will be able to follow the analysis of these accidents made nowadays is the main challenge. Measurements must be taken in order not to represent only the studied cases. Considering this two ended blame, it is noticed that there are subjective mechanisms which ease the responsibility of the institutions present in the typical working accidents. Following the capitalist ideas, the fact that human beings are being treated as work force and economic resources only, makes the working place and this process as simple contingencies.